Difference of late potentials detected by signal-averaged ECG in patients with spontaneous or drug-induced type 1 electrocardiogram pattern of Brugada syndrome - Agostinho, J. A. Ribeiro (2018)
Published on behalf of the European Society of Cardiology. All rights reserved. © The Author 2017.